EFFECT OF NUTRIENT SOLUTION ON GROWTH AND YIELD OF CHERRY TOMATO VARIETIES IN SOILLESS CULTURE - Ali, Shahajahan; Rahman, Jahedur; Islam, Nazrul; Ali, Razzab; Hossain, Mofazzal; Ali, Mokshed; Ahmed, Sujat; Sultana, Chand (International Journal of Research -GRANTHAALAYAH, 2021)
Nutrient solution and its nutritional compositions may have the effect on growth and fruit quality attributes of cherry tomato. To avoid the build-up of toxins, mineral deficiencies, nutrition abnormalities, or the spread of disease, producers should use optimum level of nutrient solution. Therefore, the present experiment was conducted to identify a suitable strength of nutrient solution for cherry tomato in hydroponic system. Treatment considered six levels of nutrient solution [viz., S1: ½ strength Rahman and Inden (2012), S2: ¾ strength Rahman and Inden (2012), S3: Full strength Rahman and Inden (2012), S4: ½ strength Hoagland and Arnon No. 2(1940), S5: ¾ strength Hoagland and Arnon No. 2 (1940) and S6: Full strength Hoagland and Arnon No. 2 (1940)] and two varieties [viz., V1: Local market cherry tomato (red), V2: Irelands cherry tomato (yellow)]. Growth and yield contributing characters, quality parameters, physiological traits and biochemical composition were analyzed. The maximum plant height, number of leaves per plant, first flowering, number of flowers per cluster, number of fruit per cluster, number of cluster per plant, average individual fruit weight and average cluster weight per plant were found in S3. Meanwhile, V2 performed better in respect of plant height, number of leaves per plant, first flowering, number of flowers per cluster, number of fruit per cluster, number of cluster per plant, average individual fruit weight and average cluster weight per plant. Therefore, cherry tomato cv. V2 can be cultured in hydroponic system with applying S3 (Full strength Rahman and Inden nutrient solution).